Sistem Pustakawan Berbasis WEB - Abel Amanda Ardelia; Ananda Aufa Rafiqi; Rais Nur Saputra (Journal of Research and Publication Innovation, 2024)
A library is a room managed by an educational institution that is used as a place of learning that provides various kinds of book collections. A school is a building or institution for learning and teaching facilities and infrastructure as well as a place for students to receive and give lessons. To create a library that is well organized and systematic. Then the library must have a web-based library application, which can provide convenience for the process of borrowing or searching for books in the school library. This website-based library application is made as a solution for schools that do not have financial adequacy. The result of this research is a service provider that can be accessed by the website. The services available on the website can be fully accessed by librarians including registering new users, logging in users, inputting books, inputting members, recording borrowing and returning books that are more recorded. For the admin's view, including registering librarians, approving requests to add the number of librarian books, and collecting payments for adding the number of books.